The NBDY Microprotein Regulates Cellular RNA Decapping - Na, Zhenkun; Luo, Yang; Schofield, Jeremy A; Smelyansky, Stephanie; Khitun, Alexandra; Muthukumar, Sowndarya; Valkov, Eugene; Simon, Matthew D; Slavoff, Sarah A (Biochemistry (Easton), 2020)
Proteogenomic identification of translated small open reading frames in humans has revealed thousands of microproteins, or polypeptides of fewer than 100 amino acids, that were previously invisible to geneticists. Hundreds of microproteins have been shown to be essential for cell growth and proliferation, and many regulate macromolecular complexes. One such regulatory microprotein is NBDY, a 68-amino acid component of the human cytoplasmic RNA decapping complex. Heterologously expressed NBDY was previously reported to regulate cytoplasmic ribonucleoprotein granules known as P-bodies and reporter gene stability, but the global effect of endogenous NBDY on the cellular transcriptome remained undefined. In this work, we demonstrate that endogenous NBDY directly interacts with the human RNA decapping complex through EDC4 and DCP1A and localizes to P-bodies. Global profiling of RNA stability changes in NBDY knockout (KO) cells reveals dysregulated stability of more than 1400 transcripts. DCP2 substrate transcript half-lives are both increased and decreased in NBDY KO cells, which correlates with 5′ UTR length. NBDY deletion additionally alters the stability of non-DCP2 target transcripts, possibly as a result of downregulated expression of nonsense-mediated decay factors in NBDY KO cells. We present a comprehensive model of the regulation of RNA stability by NBDY.